NILAI-NILAI PENDIDIKAN ISLAM DALAM KISAH THALUT DAN JALUT DALAM KAJIAN SURAH AL-BAQARAH AYAT 246-252 - Hafizah Fitri Rambe, Achyar Zein, Zulheddi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
ABSTRACT: This research aims to analyze:1) How are the values of Islamic education contained in thestory of Thalut and Jalut in the Qur’an? 2) What is the values of education contained in the story ofkingThalut and Jalut ?and 3) What is the relevance values of education in the story of king Thalut andJalut based on education now? This research uses qualitative method, with use science approach to theinterpretation of patterns analytical interpretation (analytical) which was used Holy Alquran and tafsirbook’s like: Maraghi was initiated by Ahmad bin Mustafa al-Maraghi, al-Azharwas initiated by HAMKAand al-Mishbah was initiated by M. Quraish Shihab. The results showed that: 1)Explanation of the valuescontained in the values of Islamic education in the story of Thalut and Jalut in the Alquran, are: theobligation of jihad (defending the right and the wrong), endeavoring and trusting in Allah, securing innerdetermination (never give up), being patient in any condition, optimistic to be able to achieve victory,become a wise leader, increase broad knowledge, respect the opinions of others in making decisions.2)There are five values of Islamic education in story king Thalut and Jalut in the Holy Alquran, they are:Aqidah value, syari’ah value, akhlak value, intellectual value and demonstration value. And 3) Problemsthat occur in the current condition of society are moral decadation, lazy, pessimistic, selfish, and hubbuddunyâ. These problems are relevant to the values of Islamic education in the story of Thalut and Jalut in theQur’an that with the values of Islamic education in the story of Thalut and Jalut this can change the moralcondition of humans to be better guided by the Qur’an and Hadith, increase the spirit of learning andalways active in seeking knowledge, fostering an optimistic and confident nature, fostering a nature oftolerance, and having the character of qana’ah.Penelitian ini bertujuan untuk menganalisis: 1)Bagaimana nilai-nilai pendidikan Islam yang terkandungdalam kisah Thalut dan Jalut dalam Alquran. 2)Apa nilai-nilai pendidikan yang terdapat pada kisahThalut dan Jalut dalam Alquran surah al-Baqarah ayat 246-252? dan 3)Apa relevansi nilai-nilai pendidikanyang terdapat pada kisah Thalut dan Jalut dalam Alquran surah al-Baqarah ayat 246-252 dengan kondisisaat ini?. Penelitian ini menggunakan metode kualitatif, dengan menggunakan pendekatan tafsirTahlili,yang menggunakan sumber primernya ialah Alquran. Di antara buku tafsir yang digunakan ialahtafsir al-Maragi karya Ahòmad bin Musòtòafa al-Maragi,tafsir al-Azhar karya HAMKA,tafsir al-Misbah karya M.Quraish Shihab. Hasil penelitian menunjukkan bahwa: 1) Penjelasan nilai-nilai yang terdapat dalamnilai-nilai pendidikan Islam dalam kisah Thalut dan Jalut dalam Alquran, ialah: kewajiban berjihad (membelahak dan yang bathil), berikhtiar dan bertawakkal kepada Allah, menamankan keteguhan hati dalam diri(pantang menyerah), bersabar dalam kondisi apapun, optimis untuk dapat meraih kemenangan, menjadi pemimpin yang bijaksana, meningkatkan ilmu pengetahuan yang luas, menghargai pendapat orang laindalam dalam mengambil keputusan. 2) Terdapat lima nilai pendidikan Islam dalam kisah Thalut dan Jalutdalam Alquran, ialah: nilai aqidah, nilai syari’ah, nilai akhlak, nilai intelektual dan nilai demonstrasi.3)Problematika yang terjadi pada kondisi masyarakat saat kini yaitu dekadasi moral, pemalas, pesimis,egois, danhubbud dunyâ. Problematika tersebut direlevansikan kepada nilai-nilai pendidikan Islam dalamkisah Thalut dan Jalut dalam Alquran bahwa dengan nilai-nilai pendidikan Islam dalam kisah Thalut danJalut ini dapat merubah kondisi moral manusia menjadi lebih baik yang berpedoman pada Alquran danHadis, meningkatkan semangat belajar dan senantiasa giat dalam mencari ilmu, menumbuhkan sifatoptimis dan percaya diri, menumbuhkan sifat toleransi, dan memiliki sifat qana’ah.Kata Kunci: Nilai Pendidikan Islam, Kisah Thalut dan Jalut